2023
DOI: 10.1097/rlu.0000000000004802
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-FAPI PET/CT Imaging

Akram Al-Ibraheem,
Ahmed Saad Abdlkadir,
Hasan Alalawi
et al.

Abstract: 68Ga-FAPI has been introduced recently in many nuclear medicine centers. Many pitfalls have been discussed previously. However, not all pitfalls are currently addressed in the literature. To our knowledge, this is the first reported case to address nonspecific 68Ga-FAPI expression at anorectal sphincter. A 69-year-old woman was diagnosed with intrahepatic cholangiocarcinoma. A 68Ga-FAPI scan was performed after diagnostic workup and chemoradiotherapy. In addition to 68Ga-FAPI–avid lesion at primary site, sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Radionuclide labelled, fibroblast-activated, protein inhibitors (FAPI), such as 68 Ga-FAPI, have been developed as PET tracers and show superiority to 18 F-FDG in imaging various cancers [ 13 15 ], especially in gastric cancer, pancreaticobiliary neoplasms and some rare tumors [ 16 18 ], although FAPI uptake can occur in non-oncologic conditions [ 19 , 20 ]. It was found that gastrointestinal tumors, even those containing mucus or signet ring cell carcinoma, had high FAPI uptake and these lesions could be depicted clearly [ 14 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Radionuclide labelled, fibroblast-activated, protein inhibitors (FAPI), such as 68 Ga-FAPI, have been developed as PET tracers and show superiority to 18 F-FDG in imaging various cancers [ 13 15 ], especially in gastric cancer, pancreaticobiliary neoplasms and some rare tumors [ 16 18 ], although FAPI uptake can occur in non-oncologic conditions [ 19 , 20 ]. It was found that gastrointestinal tumors, even those containing mucus or signet ring cell carcinoma, had high FAPI uptake and these lesions could be depicted clearly [ 14 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…14 Studies have also indicated that the FAPI may have the ability to distinguish between malignant and benign conditions based on uptake patterns, and tracer uptake kinetics. 15 Recent research has highlighted the potential of the FAPI for noninvasive assessment of various systemic diseases, including immunoglobulin G4-related diseases, rheumatoid arthritis, myocarditis, and pancreatitis. 8…”
mentioning
confidence: 99%
“…10 Despite their potential benefits, FAPI imaging faces inherent challenges and limitations. 11 Diagnostically, the FAPI has been found to have suboptimal specificity for detecting malignant tumors. The interindividual variability underscores the varying levels of FAP expression in different diseases and even within the same disease.…”
mentioning
confidence: 99%